The core features and outcomes of a specialised camp programme for children with life-limiting conditions and their families: A qualitative multi-perspective approach. (8th October 2019) - Mulligan, Shane; Guerin, Suzanne; McKiernan, Aidan; Brown, Anna; Hartnett, Michelle; Gray, Dee; Kiernan, Gemma
Previous research has reported that the families of children with enduring and life-limiting health conditions are at risk of negative psychosocial effects. Adjunct to medical interventions, specialist camp programmes have been developed to promote familial adjustment. However, limited research has been carried out in this area. The aim of this study was to describe the core features and outcomes of a specialised camp programme for children with life-limiting conditions (LLC) and their family. Semi-structured interviews were conducted with four professionals, three volunteers involved in facilitating the programme and two mothers representing families that attended the programme. Multiple perspectives were sought to gain a detailed understanding of the programme and outcomes. Data were analysed through an inductive thematic approach. There was considerable overlap among participant groups on the core features and outcomes of the programme. Thematically, core features are described in terms of familial togetherness, peer interaction, safety and positive experiences. Noted outcomes include lasting memories, continued peer relations for parents and siblings and enhancement of relationships between family members and professionals. Findings suggest that specialised camp programmes may provide families of children with LLC with positive experiences that support adjustment, although further research is required.